ANALISIS PERILAKU KEUANGAN GENERASI MILENIAL DI PT. TOYOTA MOTOR MANUFACTURING INDONESIA 1 - Eka Listiyani (2021)
The purpose of this quantitative research is to determine the effect of financial literacy and lifestyle on the financial behaviour of the millennial generation at PT. Toyota Motor Manufacturing Indonesia 1. The millennial generation at PT. Toyota Motor Manufacturing Indonesia 1 was chosen as the object in this study, with a total population of 277 employees. The sample selection used simple random sampling method, and selected 164 respondents. Data collection by distributing questionnaires via google form. PLS (Partial Least Square) analysis was used to test data analysis, both validity and reliability testing and hypothesis testing trough the Smart PLS 3 program with a significance level of 0,05. The results obtained include (1) financial literacy has a positive effect on financial behaviour, (2) lifestyle has a negative effect on financial behaviour.